Effect of Diuresis on Staphylococcus aureus Kidney Infections in Mice - Furtado, Dolores (1971)
In the Cornett strain of mice, water diuresis did not prevent hematogenous production of pyelonephritis by Staphylococcus aureus. Increased fluid intake did not affect the numbers of organisms deposited in the kidneys or the rate of growth during the first 4 hr after inoculation. Drinking the glucose solution did not enhance bacterial proliferation within the renal parenchyma. Subcutaneous injection of saline to supplement for interruption of drinking after inoculation reduced the numbers of organisms recovered in the kidneys but not sufficiently to prevent production of pyelonephritis. Incorporating penicillin as a marker indicated that fluids administered by subcutaneous injections were rapidly delivered to the kidneys. Combining diuresis with treatment did not influence the rapidity of delivery of antimicrobial to the kidneys or the length of time that it was present in the renal homogenate.